Aplikasi Steganografi Menggunakan Least Significant Bit (LSB) dengan Enkripsi Caesar Chipper dan Rivest Code 4 (RC4) Menggunakan Bahasa Pemrograman JAVA - Ade Davy Wiranata; Rima Tamara Aldisa (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The research objective is to hide messages through images using the LSB (Least Significant Bit) method and Caesar Chipper and Rivest Code 4 encryption. The LSB (Least Significant Bit) method is used as a message hiding technique in steganography where hiding hidden messages is done by changing a few bits in the segment. image with a secret message. The results of this study resulted in an implementation using the Least Significant Bit (LSB) to be applied to institutions with an interest in maintaining the confidentiality of encrypted image output, changing the image file size and sound (audio) file size.